Pedagogical Fundamentals Of Developing Intellectual And Creative Skills Of The Students (Eurasian Journal of Learning and Academic Teaching, 2022)
This article expresses feedback related to the development of intellectual and creative abilities of pupil-youth and considers the pedagogical bases